Guidelines for implementing cleaner production strategies in a natural rubber gloves manufacturing industry - Muthukannan M; S. Saravanakumar; M.T. Sambandam; Umapathi K; R. Kamalakannan (Cleaner Engineering and Technology)
Production of gloves is a highly energy-intensive and process-driven industry. It demands a significant amount of electrical as well as thermal energy. This paper presents the results and recommendations devised from an enquiry based onsite energy audit conducted in a gloves manufacturing unit. It summarizes the current energy demand of the manufacturing unit, highlights the major energy hunters, identifies energy saving and alternate energy generation possibilities, as well as proposes recommendations for betterment. The audit results for all different equipment are included in the report, along with suggested modifications and energy-saving achieved. The findings are still applicable as of the date and duration of the visit to the facility. As these businesses expand, minimizing expenses through energy-saving measures becomes especially crucial. At present, the gloves plant consumed about 291.278 MWh/month of electrical energy and 1830330 kcal/h of heat energy. The plant emits about 445.67 kg of CO2 equivalent for every metric ton of natural rubber. Based on the audit, recommendations are proposed to install energy monitoring devices and replacing energy hunting motors and V-belts with efficient ones. In addition, as a step towards green economy, it is recommended to consider implementing energy plantation and biogas generation plants. By implementing the proposed energy saving measure about 215.930 MWh of energy can be conserved per year. This accounts for about (15–40)% of overall energy saving and this directly reduces CO2 emission too.